Analysis of Company Performance Assessment Using the Balanced Scorecard - Ogi Maulana Firli; Pratami Wulan Tresna; Tetty Herawati (Owner : Riset dan Jurnal Akuntansi, 2023)
Performance is a description of the level of achievement of the implementation of a policy in realizing the goals, objectives, mission and vision of the organization contained in the work plan of an organization. Performance measurement is the periodic determination of the operational effectiveness of an organization, part of the organization and its personnel, based on predetermined goals, standards and criteria. Balanced Scorecard is an alternative method used by companies to manage company performance more comprehensively, not only limited to financial performance, but extends to non-financial performance, such as customer perspective, internal business processes, and learning and growth. This study aims to identify the company's performance appraisal with a balanced scorecard whose data were obtained from related journals in 1999–2022. The population in this study is an article on the company's performance appraisal with a balanced scorecard in the years 1099-2022 which was published on Scopus. Based on the Inclusion and Exclusion Criteria, the number of samples in this study was 18 articles. The method used in this study is a systematic mapping study (SMS). SMS is rooted in the study literature review (SLR). The SLR method is used to identify, review, evaluate, and interpret all available research with topic areas of interest to phenomena, with specific relevant research questions. With the use of the SLR method, a systematic review and identification of journals can be carried out, which in each process follows the steps or protocols that have been set. The results show that from 18 research articles that have been systematically mapped, researchers classify articles based on the research method approach with the topics discussed, namely: Balanced Scorecard with a research focus Balanced Scorecard is used to get a complete understanding of company performance (in terms of financial perspective, customer perspective, internal business processes, learning and growth) with its competitors. While the dominant method used in research on corporate performance appraisal with the balanced scorecard is the qualitative method.